Is Heightened Environmental Sensitivity Responsible for Drop in Young Adults' Rates of Driver's License Acquisition?. Issue 1 (January 2014) - Le Vine, Scott; Jones, Peter; Lee-Gosselin, Martin; Polak, John
Across a range of developed societies, rates of driver's license acquisition by young adults have fallen from their historic peak levels (which in Britain were in the early 1990s). A widely discussed hypothesis to explain this trend is that the heightened environmental sensitivity of the current cohort of young adults could be fully or in part responsible. The objective of this study was to establish whether empirical evidence provided support for this hypothesis. Public opinion polling data from Britain and the United States and British National Travel Survey microdata were statistically analyzed. No evidence was found, either from the United States or Britain, of the populace becoming increasingly inclined toward environmental protection. On the basis of longitudinal trends in public opinion polling, the opposite seemed to be true. Analysis of British National Travel Survey data (n = 2, 820 unlicensed adults aged 17 to 29) showed that few young British adults without driver's licenses (approximately 1%) reported that environmental sensitivity was either the main reason or a contributory reason that they had not acquired a driver's license. By contrast, more than half (59%) of not fully licensed young British adults reported that they were either learning to drive (27%) or were put off mainly by the license acquisition testing requirements (2%) or by costs associated with motoring (30%). These findings are evidence contrary to the hypothesis that growing environmental sensitivity is responsible for falling rates of licensing of young adults, at least in Britain and the United States.